Development of sweet picked guapple - Casinto, Gladys Marie
To increase the utilization of guapple, the feasibility of developing an acceptable sweet pickles from guapple was undertaken. The pickling process commonly requires a week to months. In this study, a shorter method was applied and the following variables were studied: salt and Ca(OH)2 concentrations and effects of hot packing and water bath on the acceptability of sweet pickled guapple. To test their effects on the finished product, sensory evaluation, firmness test and microbiological analysis were done. Statistical methods such as ANOVA, t-test for difference and Kramer's Rank Sum Test at 5% level of significance were used to analyze the sensory evaluation data gathered. In Phase I, through the sensory evaluation and firmness test, 5% salt in brine and 0.01% Ca(OH)2 were selected as suitable level of the said variables to be employed in curing the guapple. For Phase II, the sensory characteristics of bottled pickled guapple processed in water bathe were not significantly different from hot packed pickled guapple. However, microbiologically, the former had a lower bacterial count than the latter, therefore, processing in water bath was chosen. With the results obtained in Phase I and II, a standardized process was developed and tested for reproducibility in Phase III together with the improvement of the appearance of pickled guapple in bottles by adding strips of carrots and bell pepper.